A Synthetic Oxygen Sensor for Plants Based on Animal Hypoxia Signaling. Issue 3 (20th November 2018) - Iacopino, Sergio; Jurinovich, Sandro; Cupellini, Lorenzo; Piccinini, Luca; Cardarelli, Francesco; Perata, Pierdomenico; Mennucci, Benedetta; Giuntoli, Beatrice; Licausi, Francesco
Abstract : A biological device consisting of mammalian, fungal, and plant components drives gene expression in an oxygen-dependent manner. Abstract: Due to the involvement of oxygen in many essential metabolic reactions, all living organisms have developed molecular systems that allow adaptive physiological and metabolic transitions depending on oxygen availability. In mammals, the expression of hypoxia-response genes is controlled by the heterodimeric Hypoxia-Inducible Factor. The activity of this transcriptional regulator is linked mainly to the oxygen-dependent hydroxylation of conserved proline residues in its α-subunit, carried out by prolyl-hydroxylases, and subsequent ubiquitination via the E3 ligase von Hippel-Lindau tumor suppressor, which targets Hypoxia-Inducible Factor-α to the proteasome. By exploiting bioengineered versions of this mammalian oxygen sensor, we designed and optimized a synthetic device that drives gene expression in an oxygen-dependent fashion in plants. Transient assays in Arabidopsis ( Arabidopsis thaliana ) mesophyll protoplasts indicated that a combination of the yeast Gal4/upstream activating sequence system and the mammalian oxygen sensor machinery can be used effectively to engineer a modular, oxygen-inducible transcriptional regulator. This synthetic device also was shown to be selectively controlled by oxygen in whole plants when its components were expressed stably in Arabidopsis seedlings. We envision the exploitation of our genetically encoded controllers to generate plants able to switch gene expression selectively depending on oxygen availability, thereby providing a proof of concept for the potential of synthetic biology to assist agricultural practices in environments with variable oxygen provision.